2007 IEEE International Symposium on Industrial Electronics 2007
DOI: 10.1109/isie.2007.4375164
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Computed Tomographic Reconstruction and its Wavelet-based Segmentation by Fusion

Abstract: Abstract-In this paper, terahertz (T-ray) computed tomographic (CT) imaging [1] and segmentation techniques are investigated. The traditional filtered back projection is applied for the reconstruction of terahertz coherent tomography. A set of linear image fusion and novel wavelet scale correlation segmentation techniques is adopted to achieve material discrimination within a three dimensional (3D) object. The methods are applied to a T-ray CT image dataset taken from a plastic vial containing a plastic tube. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has also been demonstrated that the learning performance of ANNs is improved by multiresolution signal decomposition [17,18]. Application examples of multiresolution decomposition in THz signal processing include denoising [2,19], THz image compression and classification [20], and multiscale image segmentation in THz computed tomographic imaging systems [21]. In [19], THz measurements with additive noise are used to compare denoising performances of different wavelets.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that the learning performance of ANNs is improved by multiresolution signal decomposition [17,18]. Application examples of multiresolution decomposition in THz signal processing include denoising [2,19], THz image compression and classification [20], and multiscale image segmentation in THz computed tomographic imaging systems [21]. In [19], THz measurements with additive noise are used to compare denoising performances of different wavelets.…”
Section: Introductionmentioning
confidence: 99%